Homoerotismo no Brasil contemporâneo : representações, ambiguidades e paradoxos - Netto, Miguel Rodrigues de Sousa (2011)
In this work we objectify to understand the process of transformation of the social groups formed by gays, bisexuals, travesties, transsexuals and transgenders lesbians in Brazil contemporary. The invisibility of these individuals and groups, its silence and the oppression for them suffered, the constitution of a homophobic society, as well as the tenseness so that holding back and silence, injury, violence and death can be ceased, are privileged elements in this analysis. Characteristic aspects of the bourgeois society installed here, together with a fortified Christian religious tradition, are tacked to become clearer the construction of an heterosexual normative, patriarchal, male chauvinist and refusing culture that made itself hegemonic, present in the State, the education, the familiar household. The diverse actions that had aimed at/aim at to guarantee visibility and basic rights to LGBTTT individuals are analysis object, as well as the critical deepest ones to this hegemonic culture, in the elaboration of a culture that makes it opposition. For the Social History and doing vertical form to our analysis from the connective category that is the Gender, we search to understand these tenseness and the construction s possibilities of a political culture that takes to the denaturalization of the differences of the erotic-affective experiences on the way of an effectively democratic society.